A decrease in NR2B expression mediated by DNA hypermethylation induces perioperative neurocognitive disorder in aged mice. (24th January 2023) - Xu, Feifei; Cong, Peilin; Zhang, Bingqian; Dong, Hailong; Zuo, Wenqiang; Wu, Tingmei; Tian, Li; Xiong, Lize
Abstract: Aims: This study was designed to investigate the role of NR2B and the contribution of DNA methylation to NR2B expression in the pathogenesis of PND. Methods: Eighteen‐month‐old C57BL/6J mice were subjected to experimental laparotomy under 1.4% isoflurane anesthesia. Hippocampus‐dependent learning and memory were evaluated by using the Barnes maze and contextual fear conditioning tests. The protein and mRNA expression levels of NR2B were evaluated by western blotting and qRT–PCR respectively, and the methylation of the NR2B gene was examined by using targeted bisulfite sequencing. Long‐term synaptic plasticity (LTP) was measured by electrophysiology. Results: Mice that underwent laparotomy exhibited hippocampus‐dependent cognitive deficits accompanied by decreased NR2B expressions and LTP deficiency. The overexpression of NR2B in the dorsal hippocampus could improve learning and memory in mice subjected to laparotomy. In particular, the decreased NR2B expressions induced by laparotomy was attributed to the NR2B gene hypermethylation. Preoperative administration of S‐adenosylmethionine (SAM) could hypomethylate the NR2B gene, upregulate NR2B expression and improve LTP, exerting a dose‐dependent therapeutic effect against PND. Moreover, inhibiting NR2B abrogated the benefits of SAM pretreatment. Conclusions: Laparotomy cause hippocampus‐dependent cognitive decline by hypermethylating the NR2B gene, allowing us to understand the pathogenesis of PND in an epigenetic landscape. Abstract : A decrease in NR2B expression mediated by DNA hypermethylation contributes to the pathogenesis of PND in aged mice, and SAM can function as a "hypomethylating" agent to hypomethylate the NR2B gene, rather than a pure "hypermethylating" agent as it used to be predicted, exerting a dose‐dependent therapeutic effect against PND.